Ion channel expression and characterization in human induced pluripotent stem cell-derived cardiomyocytes - Zhao, Zhihan; Lan, Huan; El-Battrawy, Ibrahim; Buljubasic, Fanis; Sattler, Katherine; Yücel, Gökhan; Lang, Siegfried; Utikal, Jochen; Wieland, Thomas; Borggrefe, Martin; Zhou, Xiao-Bo; Akın, Ibrahim (Stem cells international, 2018)
Background. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are providing new possibilities for the biological study, cell therapies, and drug discovery. However, the ion channel expression and functions as well as regulations in hiPSC-CMs still need to be fully characterized. Methods. Cardiomyocytes were derived from hiPS cells that were generated from two healthy donors. qPCR and patch clamp techniques were used for the study. Results. In addition to the reported ion channels, INa, ICa-L, ICa-T, If, INCX, IK1, Ito, IKr, IKs IKATP, IK-pH, ISK1-3, and ISK4, we detected both the expression and currents of ACh-activated (KACh) and Na